Organizational Commitment and Perceived Organizational Performance Among Health Care Professionals: Empirical Evidence From A Private Hospital in Northern Cyprus - Aysen Berberoglu (Journal of Economics and Behavioral Studies, 2015)
Organizational commitment plays an important role in employee behavior. It is related with self identification of the employee with his/her organization. Self-identified employee, with higher scores of commitment, is expected to be more motivated, retaining at the organization and performing at significant levels of performance. Perceived organizational performance, on the other hand, is concerned with how employees are observing their organizations in terms of success, sustainability and development. The aim of this study was to assess the hypothesized relationship between organizational commitment and perceived organizational performance among health care professionals, by taking a small-sized private hospital in North Cyprus as the setting. The study was conducted by utilizing structured, self-administered questionnaires and collected data was analyzed by using SPSS. Study revealed that in this case, there is a positive significant relationship between organizational commitment and perceived organizational performance and organizational commitment is affecting the perceived organizational performance of the health care workers.